Metal organic framework (MOF)-based composite filler incorporated thin film nanocomposite of hollow fiber membrane for carbon dioxide permeance. (2022) - Fajrina, N.; Yusof, N.; Ismail, A.F.; Jaafar, J.; Aziz, F.; Salleh, W.N.W.
Abstract: Composite filler dispersed in a selective layer has gather significant attention for gas separation because of potential in material robustness as well as enhancement in gas permeance and selectivity. Herein, this work focused on fabrication of metal–organic framework (MOF)-based composite filler incorporated thin film nanocomposite (TFN) of hollow fiber membrane using interfacial polymerization for CO2 permeance. Layered double hydroxide (LDH)@UiO-66-NH2 MOF composite fillers were developed and incorporated into polyamide selective layer, which were coated on the polysulfone substrate. The fabricated membranes were analyzed for ATR-FTIR and contact angle, and experimented for CO2 and CH4 permeation. It is noted that the TFN membrane both increased CO2 permeance and CO2 /CH4 selectivity when comparing to thin film composite membrane. According to the results, composite filler combining MOF and LDH has future opportunities to adjust and increase the effectiveness of polymeric membranes for CO2 separation.